2018
DOI: 10.1042/bcj20180043
|View full text |Cite
|
Sign up to set email alerts
|

Protein CoAlation and antioxidant function of coenzyme A in prokaryotic cells

Abstract: In all living organisms, coenzyme A (CoA) is an essential cofactor with a unique design allowing it to function as an acyl group carrier and a carbonyl-activating group in diverse biochemical reactions. It is synthesized in a highly conserved process in prokaryotes and eukaryotes that requires pantothenic acid (vitamin B5), cysteine and ATP. CoA and its thioester derivatives are involved in major metabolic pathways, allosteric interactions and the regulation of gene expression. A novel unconventional function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
138
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(143 citation statements)
references
References 57 publications
4
138
0
1
Order By: Relevance
“…This difference is hypothesized to reflect the portion of CoA synthesis that is specifically attributable to pantothenate kinase 2. We further suggest that regulation of expression of the CoA synthase gene can be controlled by levels of substrate, 4′‐phosphopantetheine, and product, CoA, either directly or possibly via the CoAlation of transcription factors or regulatory proteins (Tsuchiya et al , , ; Gout, ).…”
Section: Discussionmentioning
confidence: 93%
“…This difference is hypothesized to reflect the portion of CoA synthesis that is specifically attributable to pantothenate kinase 2. We further suggest that regulation of expression of the CoA synthase gene can be controlled by levels of substrate, 4′‐phosphopantetheine, and product, CoA, either directly or possibly via the CoAlation of transcription factors or regulatory proteins (Tsuchiya et al , , ; Gout, ).…”
Section: Discussionmentioning
confidence: 93%
“…The role of CoA in ferroptosis sensitivity remains to be further determined. This thiol can act as a cellular antioxidant (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to an inhibitory effect on Aurora A activity, CoAlation at Cys 290 may serve other regulatory purposes. First, CoA modification might protect Cys 290 from overoxidation, which may lead to an irreversible loss of function and subsequent inactivation and/or degradation of Aurora A. The widespread ability of CoA to act as a low-molecular-weight antioxidant in response to oxidative and metabolic stress in prokaryotic and eukaryotic cells has been recently demonstrated (Tsuchiya et al, 2017, Tsuchiya et al, 2018. In these studies, in vitro CoAlation of the catalytic Cys 151 in glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was shown to protect this essential glycolytic enzyme against irreversible overoxidation and the associated loss of activity.…”
Section: What Is the Biological Function Of Aurora A Coalation?mentioning
confidence: 99%
“…This recent discovery was only possible with the development of unique research tools and methodologies, which revealed protein CoAlation as a widespread and reversible PTM involved in cellular redox regulation (Malanchuk et al, 2015). To date, more than one thousand proteins have been found to be CoAlated in a variety of prokaryotic and eukaryotic cells (Tsuchiya et al, 2017, Tsuchiya et al, 2018. Protein CoAlation occurs at a low level in exponentialy growing cells, but is strongly induced in reponse to various oxidising agents, including H2O2, diamide, menadione and t-butyl hydroperoxide.…”
Section: Introductionmentioning
confidence: 99%